An Initial Study on the Awareness of Digital Currency Among Youth - Nadzir, Maslinda Mohd; Kai, Ong Hong; Rou, Chow Jia; Hanis, Nur Asfa (STIE Malangkucecwara, 2024)
In the past two decades, the digital landscape has witnessed the emergence of digital currencies. These digital currencies, lacking physical form, facilitate online payments and direct Internet transactions for goods and services without the need for traditional banks or intermediaries. Despite the increasing popularity of digital currencies, a notable challenge persists due to the widespread lack of understanding and awareness, especially in developing countries. Nonetheless, this obstacle can be overcome through directed educational and awareness campaigns. As a result, an initial study into youth awareness of digital currencies, also known as cryptocurrencies in this article, has been carried out. This initial study on awareness surveys respondents' experiences with and trust in cryptocurrencies. A survey was conducted by distributing an online questionnaire, employing a stratified sampling method, resulting in 80 responses from youth in the Northern states of Malaysia. The survey results indicate that 39% of the respondents had less than one year of experience using cryptocurrencies, while 27% reported no prior experience. Despite the limited experience of most respondents with cryptocurrencies, the survey findings imply that most respondents trust the investment benefits of cryptocurrencies. In conclusion, the importance of ongoing research endeavours, particularly within Malaysia, cannot be understated in comprehensively understanding the factors that influence the utilisation of cryptocurrencies.